석탄광산배수처리슬러지에 Na와 S를 첨가하여 개량한 흡착제의 세슘 흡착 특성 규명 - 전소영; 김단우; 변정현; 신대현; 양민준; 이민희 (자원환경지질, 2023)
Most of previous cesium (Cs) sorbents have limitations on the treatment in the large-scale water system having low Cs concentration and high ion strength. In this study, the new Cs sorbent that is eco-friendly and has a high Cs removal efficiency was developed by improving the coal mine drainage treated sludge (hereafter 'CMDS') with the addition of Na and S. The sludge produced through the treatment process for the mine drainage originating from the abandoned coal mine was used as the primary material for developing the new Cs sorbent because of its high Ca and Fe contents. The CMDS was improved by adding Na and S during the heat treatment process (hereafter 'Na-S-CMDS' for the developed sorbent in this study). Laboratory experiments and the sorption model studies were performed to evaluate the Cs sorption capacity and to understand the Cs sorption mechanisms of the Na-S-CMDS. The physicochemical and mineralogical properties of the Na-S-CMDS were also investigated through various analyses, such as XRF, XRD, SEM/EDS, XPS, etc. From results of batch sorption experiments, the Na-S-CMDS showed the fast sorption rate (in equilibrium within few hours) and the very high Cs removal efficiency (> 90.0%) even at the low Cs concentration in solution (< 0.5 mg/L). The experimental results were well fitted to the Langmuir isotherm model, suggesting the mostly monolayer coverage sorption of the Cs on the Na-S-CMDS. The Cs sorption kinetic model studies supported that the Cs sorption tendency of the Na-S-CMDS was similar to the pseudo-second-order model curve and more complicated chemical sorption process could occur rather than the simple physical adsorption. Results of XRF and XRD analyses for the Na-S-CMDS after the Cs sorption showed that the Na content clearly decreased in the Na-S-CMDS and the erdite (NaFeS2·2(H2O)) was disappeared, suggesting that the active ion exchange between Na+ and Cs+ occurred on the Na-S-CMDS during the Cs sorption process. From results of the XPS analysis, the strong interaction between Cs and S in Na-S-CMDS was investigated and the high Cs sorption capacity was resulted from the binding between Cs and S (or S-complex). Results from this study supported that the Na-S-CMDS has an outstanding potential to remove the Cs from radioactive contaminated water systems such as seawater and groundwater, which have high ion strength but low Cs concentration. 수계 내 세슘(cesium: Cs)을 제거하기 위하여 개발된 대부분의 기존 Cs 흡착제들은 원재료 값이 고가라는 단점과, 해수와 같이 높은 이온 강도와 낮은 Cs 농도를 가지는 대규모의 오염수를 실질적으로 정화하는데 한계를 가지고 있었다. 본 연구에서는 석탄광산배수를 처리하는 과정에서 생성되는 슬러지(CMDS)에 Na와 S를 첨가하여 친환경적이고 높은 Cs 제거 효율을 가지는 Cs 흡착제를 개발하였다. Fe 및 Ca 함량이 풍부한 CMDS를 1차 소재로 사용하였고, 열처리 과정으로 Na와 S를 첨가하여 새로운 Cs 흡착제를 제조하였다(이하 본 연구에서 개발한 흡착제는 Na-S-CMDS라 명명함). Na-S-CMDS의 Cs 흡착능 및 흡착 기작을 평가하기 위해 실험실 규모의 실험과 흡착 동역학 및 등온 모델링 연구를 수행하였으며, XRF, XRD, SEM/EDS, XPS 등의 분석을 통해 Na-S-CMDS의 물리화학적, 광물학적 특성을 조사함으로써 Cs 흡착 기작을 규명하였다. 흡착 배치 실험 결과, Cs은 빠르게 Na-S-CMDS에 흡착되어 1시간 내 평형에 도달하였으며, 낮은 Cs 농도(0.5 mg/L) 조건에서도 높은 Cs 제거 효율(> 90.0%)을 보였다. 흡착 등온 모델링 결과, 단일 흡착을 가정하는 Langmuir 흡착 등온 모델에 대응되는 경향을 보였으며, 흡착 동역학 모델링 결과 흡착 경향이 유사 2차 속도(pseudo second order kinetic) 모델과 일치하는 경향을 보였고, 이러한 결과는 단순한 물리적 흡착보다 이온 교환과 같은 화학적 흡착이 우세함을 의미한다. 고농도의 Cs 용액으로 반응시킨 Na-S-CMDS의 XRF/XRD 분석 결과, Na-S-CMDS 내 Na 함량은 감소하고 흡착 전 존재하던 erdite (NaFeS2·2(H2O))가 관찰되지 않는 것을 통해, Na+과 Cs+ 사이에서 활발한 이온 교환 반응이 진행되었음을 알 수 있었다. XPS 분석 결과, Na-S-CMDS에서 Cs와 S 사이의 강한 결합 작용이 관찰되었으며, 이러한 Cs와 S(또는 S-복합체)내 결합에너지 감소도 Na-S-CMDS의 Cs 흡착능을 증가시키는 요인으로 판단되었다. 본 연구를 통해 기존에 폐기물로 처리되었던 석탄광산배수슬러지를 개량하여 제조한 Na-S-CMDS는 기존의 Cs 흡착제보다 제조 비용이 저렴하고, 해수 및 지하수와 같이 이온 강도는 높지만 Cs 농도가 낮은 대규모 오염 수계에서도 Cs 흡착능이 높게 유지되어, 현장에서 효과적인 Cs 흡착제로 사용할 수 있을 것으로 기대한다.